Polyurethane acrylate-supported rGO/TiO2 electrical conductive and antibacterial nanocomposites. Issue 6 (13th April 2019) - Li, Xiaoya; Wang, Shun; Xie, Jingang; Hu, Jianfeng; Fu, Heqing
Abstract: Polyurethane acrylate (PUA)-supported rGO/TiO2 electrical conductive and antibacterial nanocomposites were synthesized via in-situ polymerization. The well-dispersed rGO/TiO2 can serve as photoinitiator and give PUA material antibacterial property at the same time. The excellent UV-curing and antibacterial activity could be explained that the synergistic effect of rGO and TiO2, which could promote the effective electron/hole separation and thus generate various reactive species. After dopped the rGO/TiO2 into the PUA matrix, the PUA film became electric conductive. The obtained nanocomposites will have promising applications in high performance antibacterial coatings. Graphical Abstract: